Bioactive abietane-type diterpenoid glycosides from leaves of clerodendrum infortunatum (Lamiaceae) - Md Josim Uddin and Daniela Russo and Md Anwarul Haque and Serhat Sezai Çiçek and Frank Sönnichsen and Luigi Milella and Christian Zidorn (Molecules, 2021)
In this study, two previously undescribed diterpenoids, (5R,10S,16R)-11,16,19-trihydroxy-12-O-β-d-glucopyranosyl-(1→2)-β-d-glucopyranosyl-17(15→16),18(4→3)-diabeo-3,8,11,13-abietatetraene-7-one (1) and (5R,10S,16R)-11,16-dihydroxy-12-O-β-d-glucopyranosyl-(1→2)-β-d-glucopyranosyl-17(15→16),18(4→3)-diabeo-4-carboxy-3,8,11,13-abietatetraene-7-one (2), and one known compound, the C13-nor-isoprenoid glycoside byzantionoside B (3), were isolated from the leaves of Clerodendrum infortunatum L. (Lamiaceae). Structures were established based on spectroscopic and spectrometric data and by comparison with literature data. The three terpenoids, along with five phenylpropanoids: 6′-O-caffeoyl-12-glucopyranosyloxyjasmonic acid (4), jionoside C (5), jionoside D (6), brachynoside (7), and incanoside C (8), previously isolated from the same source, were tested for their in vitro antidiabetic (α-amylase and α-glucosidase), anticancer (Hs578T and MDA-MB-231), and anticholinesterase activities. In an in vitro test against carbohydrate digestion enzymes, compound 6 showed the most potent effect against mammalian α-amylase (IC50 3.4 ± 0.2 μM) compared to the reference standard acarbose (IC50 5.9 ± 0.1 μM). As yeast α-glucosidase inhibitors, compounds 1, 2, 5, and 6 displayed moderate inhibitory activities, ranging from 24.6 to 96.0 μM, compared to acarbose (IC50 665 ± 42 μM). All of the tested compounds demonstrated negligible anticholinesterase effects. In an anticancer test, compounds 3 and 5 exhibited moderate antiproliferative properties with IC50 of 94.7 ± 1.3 and 85.3 ± 2.4 μM, respectively, against Hs578T cell, while the rest of the compounds did not show significant activity (IC50 > 100 μM).
Keywords: Antidiabetic; Breast cancer; Clerodendrum infortunatum; Phenylpropanoids; Terpenoids